Lingkungan Rumah Berhubungan dengan Malaria pada Ibu Hamil - Susi Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between the home environment and malaria in pregnant women. The method used in this study is a quantitative study with a cross-sectional approach. The results showed that more pregnant women had malaria as much as 65.2%, there were standing water as much as 50.0%, there were bushes as much as 54.3%, they did not use wire netting as much as 52.2%, they did not use ceilings as much as 60.9% and not using tight walls as much as 56.5%. In conclusion, a significant relationship exists between the home environment and malaria in pregnant women. Keywords: Pregnant Women, Home Environment, Malaria